Current state of self-financing of private non-profit organizations in the conditions of the Slovak Republic - Svidroňová, Mária; Vaceková, Gabriela (Technological and Economic Development of Economy, 2012)
Ensuring the financial stability of non-profit organizations through financial decision in the structure of financial resources is influenced by many objective and subjective factors. However, a necessary presumption of financial stability is to reduce their dependence on one source of funding or in other words, the independence can be achieved by diversifying of the funding sources. And it is the diversification of financial sources and their acquisition through self-financing that we consider as an appropriate way to achieve financial balance and thus long-term existential security of non-profit organizations. This scientific paper presents the partial results of a research of the current state of self-financing and diversification of financial resources of private non-profit organizations in the Slovak Republic. We analysed the primary data by the relevant scientific methods and procedures (selected mathematical-statistical methods, analysed in SPSS – Statistical Package for the Social Sciences). With the analysis we acquired a knowledge which allows us to formulate several solutions and recommendations for theory and practice. By presenting these conclusions we fulfil a scientific goal of the paper, which is to present partial results of research of current state of funding of private non-profit organizations and interpret the obtained outputs in an economic and social context.